High Performance Torque Control of BLDC Motor - Noor Azam, Ahmad Faiz; Jidin , Auzani; Said, Mohamed Azmi; JOPRI, MOHD HATTA; Manap, Mustafa (2013)
This paper presents a simulation study using Matlab introducing Direct Torque Control (DTC) method which is implemented on BLDC motor. BLDC motor is well known and has been widely used in the industrial area due to the high speed and power density. Electronic commutation is by far more favourable compare to the conventional DC motor which uses brushes and commutators that wears and tears by time. However, a precise controller is required in order to control the switches prior to commutation process. DTC of BLDC combines a simple control method and a demanding motor to complete a better drives system. Based on in depth analysis of BLDC mathematical model and the operation of DTC system, a simulation model is developed using Matlab/Simulink. The capability and performance of torque and flux control of the drive system is verified.